The relation of feathering and overflow fat of lamb carcasses to the grade of the lamb, degree of marbling, and market value of the lamb - Mackintosh, D.L.; Merkel, R.A.; Menzies, C.S. (Kansas Agricultural Experiment Station, 2011)
This project was undertaken in the spring of 1960 in an endeavor to determine the relationship, if any, of internal fats, overflow, and feathering to the degree of marbling in the longissimus dorsi muscle (eye muscle), the grade of the carcass; and the relationship of marbling to the palatability of meat.
Keywords: Sheep; Feathering; Carcasses; Grade; Marbling; Market value